An investigation of factors influencing freeze lining behaviour. Issue 4 (2nd October 2018) - Crivits, Tijl; Hayes, Peter C.; Jak, Evgueni
ABSTRACT: Recent studies have indicated that the steady state thicknesses and interface temperatures of freeze linings can be influenced by factors other than the thermal parameters of the systems. To explore these possibilities further cold modelling of freeze linings was undertaken in the CaCl2 –H2 O system using an experimental apparatus that enabled the variation of both the bath temperature and the fluid flow rate. Through in situ experimental observations, it was shown that the phases formed, the deposit/liquid interface temperature and the freeze lining thicknesses depend strongly on chemical parameters and elementary reaction steps, which are not considered by the conventional thermal treatment of freeze linings. These results indicate the need for further systematic investigation of various process parameters that influence the elementary reaction steps that may be active in these systems under dynamic steady state conditions.